Liečba inveterovanej zadnej luxácie ramena anatomickou totálnou protézou - Popelka, Vladimír (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2016)
The aim of this study was to present the results of surgical treatment in two male patients with chronic locked posterior dislocation of the shoulder, who underwent total shoulder arthroplasty due to destruction of more than 45% of the humeral head articular surface and glenoid impairment. The deltopectoral approach was used in both cases. Total shoulder arthroplasty (Epoca-Synthes) was carried out in the standard manner. Case one: A 29-year-old, extremely obese patient suffered injury to his shoulder during an epileptic seizure. At 11 months after injury, surgery was performed using an interscalene plexus block because general anaesthesia presented a high risk for the patient. The total follow-up period was 4 years. Between the 2nd and the 3rd follow-up year, the patient lost about 46% of his body weight. At the first year, when the patient maintained his initial overweight, shoulder elevation was 170° and range of motion was not restricted. The overall Constant Score (CS) was 96. Due to a massive weight loss, muscle strength was reduced and the CS decreased to 82. Case two: A 41- year-old man injured his shoulder in a fall and, due to a late diagnosis, underwent surgery under general anaesthesia at 11 months after injury. At 3-year follow-up the overall result was excellent, with only slightly limited internal rotation of the shoulder.
Keywords: Shoulder Dislocation; artroplastika ramenního kloubu; dospělí; Adult; Shoulder Joint; Follow-Up Studies; výsledek terapie; Humans; mužské pohlaví; Male; lidé; Shoulder Injuries; luxace ramenního kloubu; Arthroplasty, Replacement, Shoulder; ramenní kloub; poranění ramene; Treatment Outcome; následné studie